Revitalisasi Pasar: Apa Selanjutnya? - Abdurrahman Arif (Journal of Research and Development on Public Policy, 2024)
Market revitalization is not only physical development. Management, economic and social development is needed. The phenomenon of contemporary coffee shops appearing in traditional markets has attracted researchers to identify market revitalization problems. The aim of this research is to identify problems regarding revitalization. The research perspective is what the problem is, what is the government's attitude and what is the orientation of policy holders. Literature review method to verify data related to the implementation of revitalization in a number of markets. Shows that there are still problems such as communication and perceptions about revitalization, while policy holders have shown a clear policy direction. Market classification and revitalization that must be carried out.